Identifikasi, Implementasi, dan Strategi Pengembangan Pariwisata Syariah di Kota Banda Aceh (Studi Kasus Kecamatan Baiturrahman) - Uswatunhasanah -; Zahrul Fuady; Myna Agustina Y (Jurnal RAUT, 2023)
Baiturrahman District is a service center for cultural and religious tourism destinations in Banda Aceh City. The purpose of this study is to identify tourism objects that are in accordance with the sharia concept, to know the implementation of the sharia tourism concept and to know the sharia tourism development strategy in Baiturrahman District. This research was conducted using qualitative methods. The data processing techniques used are descriptive quantitative analysis techniques to determine tourist attractions that meet the criteria for sharia tourism objects, qualitative descriptive analysis to determine the application of sharia tourism concepts, and SWOT analysis (strengths, weaknesses, opportunities, and threats) to determine sharia tourism development strategies in Baiturrahman District. The results show that the application of the concept of sharia tourism in Baiturrahman District has not been maximized. There are several criteria for sharia tourism objects that are not yet found in tourist attraction. There are no halal-certified accommodation and spa, sauna, massage facilities in Baiturrahman District, but their implementation has followed sharia principles. Currently, the Banda Aceh city government is drafting a Qanun related to sharia tourism and collaborating between agencies and business actors to improve the implementation of sharia tourism. The strategy for developing sharia tourism in Baiturrahman District is to promote, socialize, disseminate information, provide, and improve sharia tourism supporting facilities, and enforce Islamic law in every aspect of tourism.